2016
DOI: 10.36685/phi.v2i3.76
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Suspected Peripheral Neuropathy Outbreak in Dechentsemo Central School, Thinleygang, Punakha

Abstract: Background: A suspected peripheral neuropathy outbreak was reported from Dechentsemo Central School, Thinleygang, Punakha, following which the investigation team was immediately dispatched in the field.Objective: The aim of investigation was to ascertain the cause and risk factor for the outbreak in order to implement control measures.Methods: A case control study was devised for the investigation to study about the past exposure or deficiencies in order to find out the suspected cause and risk factors.  A sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The current outbreak was dominated by males (68%) and this could be because two of the three events occurred in institutes with high proportion of male, unlike in a previous study which found that all PN cases were female. 10 We also found that there was no significant difference in average ThDP level among the different age groups. Despite all the current outbreaks being reported from the Eastern region of the country, the limited sample size prevents generalizing thiamine outbreaks to this particular geographical location.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The current outbreak was dominated by males (68%) and this could be because two of the three events occurred in institutes with high proportion of male, unlike in a previous study which found that all PN cases were female. 10 We also found that there was no significant difference in average ThDP level among the different age groups. Despite all the current outbreaks being reported from the Eastern region of the country, the limited sample size prevents generalizing thiamine outbreaks to this particular geographical location.…”
Section: Resultsmentioning
confidence: 53%
“…9 Thiamine deficiency cases have previously been reported in Bhutan affecting young school-going students with loss of productive time and a few reported deaths. 10,11 Pradhan et al, (2021) found that infantile beriberi was the main cause of infant mortality (>70%) in Bhutan. 12 In 2017 several sporadic thiamine deficiency outbreaks were recorded in Bhutan among school children, thus fortified rice supplementation was initiated.…”
Section: Introductionmentioning
confidence: 99%